The Janus Face of Follicular T Helper Cells in Chronic Viral Infections - Greczmiel, Ute; Oxenius, Annette (Frontiers in Immunology, 2018)
Chronic infections with non-cytopathic viruses constitutively expose virus-specific adaptive immune cells to cognate antigen, requiring their numeric and functional adaptation. Virus-specific CD8 T cells are compromised by various means in their effector functions, collectively termed T cell exhaustion. Alike CD8 T cells, virus-specific CD4 Th1 cell responses are gradually downregulated but instead, follicular T helper cell (TFH) differentiation and maintenance is strongly promoted during chronic infection. Thereby, the immune system promotes antibody responses, which bear less immune-pathological risk compared to cytotoxic and pro-inflammatory T cell responses. This emphasis on TFH cells contributes to tolerance of the chronic infection and is pivotal for the continued maturation and adaptation of the antibody response, leading eventually to the emergence of virus-neutralizing antibodies, which possess the potential to control the established chronic infection. However, sustained high levels of TFH cells can also result in a less stringent B cell selection process in active germinal center reactions, leading to the activation of virus-unspecific B cells, including self-reactive B cells, and to hypergammaglobulinemia. This dispersal of B cell help comes at the expense of a stringently selected virus-specific antibody response, thereby contributing to its delayed maturation. Here we discuss these opposing facets of TFH cells in chronic viral infections.